Role of Factor XIa and Plasma Kallikrein in Arterial and Venous Thrombosis - Visser, Mayken; Heitmeier, Stefan; ten Cate, Hugo; Spronk, Henri M. H. (Thrombosis and Haemostasis, 2020)
Cardiovascular disease, including stroke, myocardial infarction, and venous thromboembolism, is one of the leading causes of morbidity and mortality worldwide. Excessive coagulation may cause vascular occlusion in arteries and veins eventually leading to thrombotic diseases. Studies in recent years suggest that coagulation factors are involved in these pathological mechanisms. Factors XIa (FXIa), XIIa (FXIIa), and plasma kallikrein (PKa) of the contact system of coagulation appear to contribute to thrombosis while playing a limited role in hemostasis. Contact activation is initiated upon autoactivation of FXII on negatively charged surfaces. FXIIa activates plasma prekallikrein (PK) to PKa, which in turn activates FXII and initiates the kallikrein–kinin pathway. FXI is also activated by FXIIa, leading to activation of FIX and finally to thrombin formation, which in turn activates FXI in an amplification loop. Animal studies have shown that arterial and venous thrombosis can be reduced by the inhibition of FXI(a) or PKa. Furthermore, data from human studies suggest that these enzymes may be valuable targets to reduce thrombosis risk. In this review, we discuss the structure and function of FXI(a) and PK(a), their involvement in the development of venous and arterial thrombosis in animal models and human studies, and current therapeutic strategies.
Keywords: factor XI; plasma kallikrein; thrombosis; animal models; clinical studies